The internal displacement crisis in Africa : implementation of national and international law on the child marriage phenomenon in Uganda - Baydas, Lana (University of Pretoria, 2008)
Mini Dissertation (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2007.